Diffusion-Weighted MR Imaging in a Prospective Cohort of Children with Cerebral Malaria Offers Insights into Pathophysiology and Prognosis - Moghaddam, S.M.; Birbeck, G.L.; Taylor, T.E.; Seydel, K.B.; Kampondeni, S.D.; Potchen, M.J. (American Journal of Neuroradiology, 2019)
BACKGROUND AND PURPOSE: Validation of diffusion-weighted images obtained on 0.35T MR imaging in Malawi has facilitated meaningful review of previously unreported findings in cerebral malaria. Malawian children with acute cerebral malaria demonstrated restricted diffusion on brain MR imaging, including an unusual pattern of restriction isolated to the subcortical white matter. We describe the patterns of diffusion restriction in cerebral malaria and further evaluate risk factors for and outcomes associated with an isolated subcortical white matter diffusion restriction.MATERIALS AND METHODS: Between 2009 and 2014, comatose Malawian children admitted to the hospital with cerebral malaria underwent admission brain MR imaging. Imaging data were compiled via NeuroInterp, a RedCap data base. Clinical information obtained included coma score, serum studies, and coma duration. Electroencephalograms were obtained between 2009 and 2011. Outcomes captured included death, neurologic sequelae, or full recovery.RESULTS: One hundred ninety-four/269 (72.1%) children with cerebral malaria demonstrated at least 1 area of diffusion restriction. The most common pattern was bilateral subcortical white matter involvement (41.6%), followed by corpus callosum (37.5%), deep gray matter (36.8%), cortical gray matter (17.8%), and posterior fossa (8.9%) involvement. Sixty-one (22.7%) demonstrated isolated subcortical white matter diffusion restriction. These children had lower whole-blood lactate levels (OR, 0.9; 95% CI, 0.85–0.98), were less likely to require anticonvulsants (OR, 0.6; 95% CI, 0.30–0.98), had higher average electroencephalogram voltage (OR, 1.01; 95% CI, 1.00–1.02), were less likely to die (OR, 0.09; 95% CI, 0.01–0.67), and were more likely to recover without neurologic sequelae (OR, 3.7; 95% CI, 1.5–9.1).CONCLUSIONS: Restricted diffusion is common in pediatric cerebral malaria. Isolated subcortical white matter diffusion restriction is a unique imaging pattern associated with less severe disease and a good prognosis for full recovery. The underlying pathophysiology may be related to selective white matter vulnerability.CMcerebral malariaIWMDRisolated subcortical white matter diffusion restrictionEEGelectroencephalogram